Comparative Antifungal Activity of Cilofungin (LY121019) against Candida Species, Including Evaluation of Susceptibility Testing Method. (1992) - Chagla, Abdul H; Hii, John H; Hoban, Daryl J; Simor, Andrew E; Ferro, Santiago; Witwicki, Evelyn; Poon, Ruby; Low, Donald E
Abstract : The in vitro activity of cilofungin against 100 Candida species was compared with 5-flucytosine. amphotericin B and ketoconazole by two laboratories independently and in a blinded fashion using a macrotitre dilution broth method in saam-f medium. Cilofungin showed good in vitro activity against Candida albicans. Candida tropicalis and Candida glabrata (90% minimal inhibitory concentration [MIC] 3.2 μg/mL) but was inactive against other Candida species. When testing the susceptibility of cilofungin, 5-flucytosine and amphotericin B at the two centres, approximately 90% of the Candida strains had MICs differing by fourfold or less. However, when testing susceptibility of ketoconazole, only 51% of the Candida strains had MIC differences fourfold or less. MIC susceptibility testing with cilofungin, 5-flucytosine and amphotericin B in saam-f medium is reproducible.